Quantitative comparison of strategies to delay clogging in straight capillaries - Pal, S.; Kulkarni, A. A. (Chemical Engineering Science, 2019)
It is challenging to achieve non-stop flow of a liquid-solid suspension through small channels as it eventually leads to clogging. This paper presents a quantitative comparison of four different techniques for enhancement of solid handling processes in microchannels of two different diameters. These techniques include dosing of the inert gas phase, dosing of the inert and immiscible liquid phase, and changing the wall wettability and multi-point injection, which, in principle, individually follow different mechanisms to delay clogging. An antisolvent based method for precipitation of salt was used to generate solid particles during flow. Clogging time at various flow rates from all the methods was measured and analysed. Irrespective of the method of delaying clogging, the scaling law of clogging time as a function of residence time was seen to remain unchanged. Among these methods, dosing of an inert, immiscible liquid has been identified as the most effective and robust method to delay clogging while enhancing transport of particles in segmented flow.